Study of the proliferation in human gastric mucosa after in vivo bromodeoxyuridine labelling. Issue 7 (July 1993) - Patel, S; Rew, D A; Taylor, I; Potten, C S; Owen, C; Roberts, S A
Abstract : Studies to measure human gastric crypt or gland cell proliferation may have a number of practical clinical applications in relation to both benign and malignant gastric conditions. Bromodeoxyuridine (BrdUrd) labels human gastric mucosal cells in the S phase. Computer aided data analysis of labelled mucosa allows static proliferative indices to be estimated, including the crypt labelling index (LI), the peak labelling position, the distribution of labelled cells and indirectly the crypt growth fraction. Multiparameter flow cytometric analysis of labelled nuclei allows the S phase duration (Ts) of mucosal cells to be estimated. Specimens of histologically normal gastric body (GB, n = 16) and antral mucosa (GA, n = 10) were obtained from 25 patients with gastric carcinomas who received a bolus dose of 250 mg BrdUrd between 3.0 and 15.7 hours before surgery. Tissue sections were stained by an immunohistochemical method and subjected to detailed counting of up to 50 longitudinal crypts per specimen. The total crypt labelling index was calculated by a grid counting method. A significant difference existed between the proliferative compartments of gastric antral and body mucosa measured by a number of criteria. The median lengths of the crypts were 137 cells (GB) and 188 cells (GA). The median peak labelling positions were cell 26 (GB) and cell 61 (GA) from the crypt orifice. The mean crypt labelling indices were 2.8% (GB) and 4.8% (GA). The mean Ts of GA cells was 7.7 hours and of GB cells was 10.8 hours.